Novel Jumbo Biopsy Forceps for Surveillance of Inflammatory Bowel Disease: A Comparative Retrospective Assessment - Kenneth Song; Daniel Toweill; Stephen J. Rulyak; Scott D. Lee (Gastroenterology Research and Practice)
Background and Study Aims. Most available jumbo cup forceps require a 3.7 mm biopsy channel, necessitating the use of standard-sized colonoscope. A newer jumbo forceps (Radial Jaw 4 Jumbo Biopsy Forceps [RJ4]) fits within a 3.2 mm biopsy channel, allowing use with a pediatric colonoscope. To assure the RJ4 did not alter biopsy adequacy, we compared the size and quality of specimens to a historical jumbo cup forceps (Radial Jaw 3 Max Capacity Biopsy Forceps, [RJ3 MC]). Patients and Methods. A retrospective comparative study of biopsies taken with either forceps. Biopsies were compared for diameter, depth, crush artifact, and acceptability for diagnosis. Results. 333 specimens were taken with RJ4 and 335 specimens with the RJ3 MC. Mean sample diameter was 4.45 mm and 4.55 mm for the RJ4 and RJ3 MC (𝑃=0.41). Mean depth of biopsies with the RJ4 was greater (𝑃<0.01). Conclusions. Biopsies from the RJ4 are similar in size and quality to biopsies from the RJ3 MC. The RJ4 has the advantage of fitting in a smaller biopsy channel.